Respuesta :

colevv

Step-by-step explanation:

Change the equation to the general form [tex]Ax + By + C = 0[/tex].

[tex]y - 15 = - 6(x + 7) \\ y - 15 = - 6x - 42 \\ 6x + y - 15 + 42 = 0 \\ 6x + y + 27 = 0[/tex]

The slope

[tex] = - \frac{A}{B} [/tex]

[tex] = - \frac{6}{1} [/tex]

[tex] = - 6[/tex]

Answer:  Slope is -6

Step-by-step explanation:

We want to rearrange the equation to the form of y=mx+b, where m is the slope and b the y-intercept.

y−15=−6(x+7)

y−15=−6x-42

y=−6x-42+15

y = -6x - 27

The slope is -6

ACCESS MORE